Editorial: Infectious diseases affecting reproduction and the neonatal period in cattle - Moore, Prando Dadin; Canton, German Jose; Louge Uriarte, Enrique Leopoldo (Frontiers Media, 2021)
Even with the global scenario after the SARS CoV-2 pandemic, human population keeps growing, and therefore food safety and quality demand is increasing. So, it is required to improve the efficiency in most livestock production systems including the cattle industry. Because the efficiency of cattle industry is far away from optimum (1–3), the intensification of the production systems emerges as a challenge. Currently, over 1 billion heads are raised in our planet. Countries like Argentina, Australia, Brazil, China, and United States extensively raise their cattle on pastures, which represents over 50% of the productive cattle stock worldwide.